Analytical Analysis and Experimental Validation of a Multi-parameter Mach-Zehnder Fiber Optic Interferometric Sensor - Lorenzo B. Scandian; Marcelo E. V. Segatto; Carlos E. S. Castellani (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
Abstract Here we report a simple analytical technique to model a Mach-Zehnder fiber optic interferometric sensors that allow us to predict and calculate via computer simulations parameters that are not easily obtained experimentally. This model was calibrated and compared with experimental data using a 120 mm sensor for measurements of temperature, refractive index and water level. For instance, we were able to calculate the effects on the cladding effective index caused by the variation of those physical parameters. Moreover, this analysis could further our understanding of such sensors and allow us to make predictions about their use in different applications and even their behavior with different sensing lengths.